Tinjauan Aspek Keselamatan pada Tikungan Rawan Kecelakaan di Jalan Raya Pekanbaru–Bangkinang KM 50: Studi Kasus: Jalan Raya Pekanbaru-Bangkinang KM 50 sepanjang 350 m - Putra Iriandi, Farel; Putra, Benny Hamdi Rhoma; Sebayang, Mardani; Siswanto (Jurnal Teknologi dan Rekayasa Sipil, 2025)
The curve at Km 50 of the Pekanbaru-Bangkinang Highway is classified as a sharp and closely spaced compound curve and is identified as an accident-prone area, marked by accident-prone zone signs on one direction of the curve. Based on traffic accident data from 2019-2024, five accidents have occurred at this location. Non-compliance of the geometric design with current standards is a contributing factor to traffic accidents. This study aims to evaluate the geometric conditions of the curve and analyze safety-related issues based on the 2021 geometric road design guidelines and other safety aspects. The results show that Curve 1 (PI-1) is categorized as an SS curve, while Curve 2 (PI-2) is an SCS curve. Other geometric features such as radius, degree of curvature, transition curve, and sight distance on both curves do not meet the geometric road design standards. Additionally, the superelevation value of PI-1 exceeds the recommended maximum value. Safety issues are further compounded by pavement damage, including patches, alligator cracks, potholes, and aggregate wear. Traffic facilities at the curve lack complete warning signs, speed limit signs, road studs, street lighting, convex mirrors, and damaged road markings. If geometric improvements are not feasible, recommendations include installing warning signs for accident-prone areas, reduced speed, road damage, and slippery surface warnings. Other measures include installing street lighting, reflectors on guardrails, speed limit signs, road studs, convex mirrors, delineator, vegetation clearing, and repairing longitudinal road markings.